Tumor Localization and Biodistribution of 99mTc-Muramylpolypeptide(MPP) in the Rat - Schümichen, C.; Weiß, H. (Nuklearmedizin - NuclearMedicine, 1986)
Muramylpolypeptide, extracted from Nocardia opaca bacteria and originally designed for immunotherapy of malignant tumors, proved to localize in malignant tumors, when labeled with 99m Tc. In the tumor-bearing rat 99m Tc-muramylpolypeptide (MPP) showed a fast turnover and optimum tumor to soft tissue ratios were obtained as early as between 30-60 min after application. The uptake mechanism in malignant tumors remains uncertain.